The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41379-019-0446-y
|View full text |Cite
|
Sign up to set email alerts
|

Multiregion exome sequencing of ovarian immature teratomas reveals 2N near-diploid genomes, paucity of somatic mutations, and extensive allelic imbalances shared across mature, immature, and disseminated components

Abstract: Immature teratoma is a subtype of malignant germ cell tumor of the ovary that occurs most commonly in the first three decades of life, frequently with bilateral ovarian disease. Despite being the second most common malignant germ cell tumor of the ovary, little is known about its genetic underpinnings. Here we performed multi-region whole exome sequencing to interrogate the genetic zygosity, clonal relationship, DNA copy number, and mutational status of 52 pathologically distinct tumor components from 10 femal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 33 publications
(41 reference statements)
3
32
0
Order By: Relevance
“…The authors show that copy neutral loss of heterozygosity results from meiotic errors at different stages that can be identified based on the copy number variation profile of individual tumors ( Figure 3C) [56]. This study also suggested that while bilateral disease arises from different clonal events, spread to the peritoneum is driven by a single clone, even in bilateral disease [56]. Seventeen patients with immature teratoma are included in the GENIE/AACR database.…”
Section: Immature Teratomamentioning
confidence: 82%
See 2 more Smart Citations
“…The authors show that copy neutral loss of heterozygosity results from meiotic errors at different stages that can be identified based on the copy number variation profile of individual tumors ( Figure 3C) [56]. This study also suggested that while bilateral disease arises from different clonal events, spread to the peritoneum is driven by a single clone, even in bilateral disease [56]. Seventeen patients with immature teratoma are included in the GENIE/AACR database.…”
Section: Immature Teratomamentioning
confidence: 82%
“…Available data suggest that MOGCTs have a low mutational burden with marked aneuploidy [42]. This pattern is hypothesized to arise from abnormal segregation of chromosomes during meiosis and/or mitosis [42,56]. A whole exome sequencing study of 24 MOGCTs found a median of 2.5 (range 0-8) non-synonymous mutations per tumor; an average of 35% of the genome was affected by copy number alterations in 87 patients.…”
Section: Malignant Ovarian Germ Cell Tumors (Mogcts)mentioning
confidence: 99%
See 1 more Smart Citation
“…Rarely, MOTs may arise in the context of ovarian teratoma. In such cases, genomic studies have shown the mucinous neoplasms to have identical genetic patterns to those of the adjacent teratoma, indicating a shared cell of origin 3,4 . Ovarian teratomas are believed to develop from a retained oocyte within the ovary.…”
Section: Figurementioning
confidence: 99%
“…Ovarian teratomas are believed to develop from a retained oocyte within the ovary. Extensive loss of heterozygosity (LOH) and an extremely low mutational burden are the genetic hallmarks of teratoma, implying meiotic abnormalities during different stages of germ cell evolution in tumour development 4–6 . Although a germ cell origin for the subset of MOTs associated with teratomas has been confirmed by multiple studies, such tumours with both mucinous and teratomatous components are rare, and the incidence of MOTs showing the genetic hallmarks of teratoma, among MOTs in which no teratoma is identified, remains unknown.…”
Section: Figurementioning
confidence: 99%